Singularities Analysis of the Jacobian Matrix Modified in the Continuation Power Flow: Performance Evaluation - Bonini Neto, A. [UNESP]; Alves, D. A. [UNESP] (Ieee-inst Electrical Electronics Engineers Inc, 2017)
In the literature, a study to analyze stability and voltage instability is related to the P-V curve (power versus voltage magnitude) and the maximum loading point (MLP) (point on the curve that separates the stable operation of the unstable). The maximum loading point may be consequent to a saddle node bifurcation (SNB) related to transmission capacity limit in an electrical system where the Jacobian matrix is singular, or limit induced bifurcation (LIB), related the reactive power limit of the generator, where the matrix is not singular. In this sense, it is presented in this second part of the paper the trajectory of the values of the determinants of the modified Jacobian matrices (vertical bar J(m)vertical bar) of these methods. A graphical analysis is also shown for a better understanding. The methods studied are: local parameterization (lambda ou V-k), global parameterization (total real power losses (Pa) and the quadratic equation in Pa plane in function of loading factor. The results are obtained to the two real large systems of 638 and 787 buses corresponding to part of South-Southeast Brazilian systems and of a 904-bus Southwestern American system.
Keywords: Voltage stability; Maximum loading point; Bifurcation; Continuation power flow; Continuation method